Effect of moderate, 30 percent global maternal nutrient reduction on fetal and postnatal baboon phenotype. Issue 6 (26th July 2017) - Li, Cun; Jenkins, Susan; Mattern, Vicki; Comuzzie, Anthony G.; Cox, Laura A.; Huber, Hillary F.; Nathanielsz, Peter W.
Abstract: Background: Most developmental programming studies on maternal nutrient reduction (MNR) are in altricial rodents whose maternal nutritional burden and offspring developmental trajectory differ from precocial non‐human primates and humans. Methods: Control (CTR) baboon mothers ate ad libitum; MNR mothers ate 70% global control diet in pregnancy and lactation. Results: We present offspring morphometry, blood cortisol, and adrenocorticotropin (ACTH) during second half of gestation (G) and first three postnatal years. Moderate MNR produced intrauterine growth restriction (IUGR). IUGR males (n=43) and females (n=28) were smaller than CTR males (n=50) and females (n=47) in many measurements at many ages. In CTR, fetal ACTH increased 228% and cortisol 48% between 0.65G and 0.9G. IUGR ACTH was elevated at 0.65G and cortisol at 0.9G. 0.9G maternal gestational weight gain, fetal weight, and placenta weight were correlated. Conclusions: Moderate IUGR decreased body weight and morphometric measurements at key time points and altered hypothalamo‐pituitary‐adrenal function.